Land selection for coffee cultivation in areas with limited information: territory spatial analysis and local knowledge - López-Carmona, Dante; Gallegos, Ángeles; Palma, David Jesús; Martín-Morales, Gustavo; Barragán-Maravilla, Monserrat; Hernández-Vallecillo, Gabriel; Bautista, Francisco (Ecosistemas y Recursos Agropecuarios, 2021)
Most of the soils of the Mixteca Alta show high levels of degradation. A strategy for its management and conservation is through integrating local knowledge and spatial analysis to delimit areas suitable for coffee production. The objective was to evaluate the aptitude of the lands to grow coffee in the Mixteca Alta, Oaxaca State, considering local knowledge and geographic information systems. A land suitability model for coffee cultivation was developed based on the analysis of the altitude, the steepness of the slope and the soil. The unsuitable coffee plantations are located in the areas with the lowest altitude, which were also the warmest and with the highest presence of rust. Also, the altitude of the land higher than 2200 meters above sea level is not suitable for growing coffee due to the presence of frost. The slope of the land greater than 80o is not suitable for growing coffee. The very suitable lands occupy only 258.1 ha; the suitable 2 030.4 ha; the moderately suitable 3 162.3 ha; marginally suitable occupy 2 558.8 ha; and the unsuitable 5 123.9 ha. Land suitable for growing coffee have deep soils with loamy-clay-sandy textures and an average leaf thickness of 5 cm. This work can serve as a reference for land evaluation in areas with scarce geographic information on the physical environment.